2013
DOI: 10.1002/bjs.9280
|View full text |Cite
|
Sign up to set email alerts
|

Renal function 5 years after open and endovascular aortic aneurysm repair from a randomized trial

Abstract: Renal function 5 years after OR and EVAR for AAA was similar. Neither surgical procedure accelerated the loss of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 34 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…2,3,5,7-11 The 5-year 77.5% survival demonstrated by the study group not suffering renal morbidity aligns with long-term results from the Dutch Randomized Endovascular Aneurysm Management (DREAM) trial. 10 Although it is an infrequent event, those patients unfortunate enough to have development or exacerbation of renal dysfunction after EVAR also demonstrate a distinct survival disadvantage. Decreased estimated life expectancy is associated with more severe renal dysfunction, as hypothesized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,7-11 The 5-year 77.5% survival demonstrated by the study group not suffering renal morbidity aligns with long-term results from the Dutch Randomized Endovascular Aneurysm Management (DREAM) trial. 10 Although it is an infrequent event, those patients unfortunate enough to have development or exacerbation of renal dysfunction after EVAR also demonstrate a distinct survival disadvantage. Decreased estimated life expectancy is associated with more severe renal dysfunction, as hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…6 An early series describing a single center’s experience in the late 1990s placed the frequency of a new HD requirement after elective EVAR at 3.5%. 7 Subsequent registry analyses and clinical trials refined this estimate to between 0.6% and 1.1% 2,3,5,8-10 ; acute and chronic kidney injuries are poorly characterized in these reports. Hua et al reported AKI appearing at a frequency of 0.9% in their National Inpatient Sample analysis, whereas Pisimisis et al identified that 17.2% of their cohort suffered a similar complication.…”
mentioning
confidence: 99%
“…The DREAM trial results only give data at the 5-year time point from 189 patients who remained available for follow-up – these data could not be used in our longest time point, which dealt with data closer to 1-year postoperatively (44). At 5 years they found that there was a mean difference in eGFR of 3.9 (95 per cent CI 1.3 to 6.5) ml per min per 1.73m2 in the EVAR group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in most of the clinical trials carried out in the population of CKD patients, the use of a simple formula that estimates renal function using only serum creatinine value is extremely helpful and has a well-established efficacy [16,17,18]. Another practical advantage resulting from the use of formulas is the possibility to calculate a reliable value of renal function in the so-called “not nephrological” areas that host a large number of patients with renal disease, such as some hospital wards (cardiology, internal medicine, etc), specialist outpatient clinics for internal diseases (diabetes mellitus, arterial hypertension, dyslipidemia) or even the offices of primary care physicians.…”
Section: Discussionmentioning
confidence: 99%